Characterization of γδ T Cells from Zebrafish Provides Insights into Their Important Role in Adaptive Humoral Immunity - Wan, Feng; Hu, Chong-bin; Ma, Jun-xia; Gao, Ke; Xiang, Li-xin; Shao, Jian-zhong (Frontiers in Immunology, 2017)
γδ T cells represent an evolutionarily primitive T cell subset characterized by distinct T cell receptors (TCRs) and innate and adaptive immune functions. However, the presence of this T cell subset in ancient vertebrates remains unclear. In this study, γδ T cells from a zebrafish (Danio rerio) model were subjected to molecular and cellular characterizations. The constant regions of zebrafish TCR-γ (DrTRGC) and δ (DrTRDC) were initially identified. Zebrafish γδ T cells accounted for 7.7–20.5% of the total lymphocytes in spleen, head kidney, peripheral blood, skin, gill, and intestine tissues. They possess typical morphological features of lymphocytes with a surface phenotype of γ+δ+CD4−CD8+. Zebrafish γδ T cells functionally showed a potent phagocytic ability to both soluble and particulate antigens. They can also act as an antigen-presenting cell to initiate antigen (KLH)-specific CD4+ TKLH cell activation and to induce B cell proliferation and IgM production. Particularly, zebrafish γδ T cells also play a critical role in antigen-specific IgZ production in intestinal mucus. These findings demonstrated that γδ T cells had been originated as early as teleost fish, which providing valuable insights into the evolutionary history of T cell subset. It is anticipated that this study would be used as a guide to develop a zebrafish model for the cross-species investigation of γδ T cell biology.